استخدام "المحفوظات" لترقية إتقان المفردات - Najib, Aan; Huda, Hisbullah; Syafi’i, Imam; Maifandi, Ikrimah (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to determine how the use of mahfudzat in increasing the maharah al-kalam of students. Researchers used qualitative methods in this study. In collecting data, the researcher used learning outcomes measurement techniques, exams, interviews, observations, and documentation. Research has shown that the use of mahfudzat can improve students’ maharah al-kalam or speaking skills. Mahfudzat is a short literary work that students study, they are assigned to memorize or memorize parts of it after studying and understanding, and they are the subject of literary studies at the elementary level, especially at the upper and intermediate levels. By using mahfudzat, students’ speaking skills are improved.